2015
DOI: 10.1186/s12871-016-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

First do no harm: pain relief for the peripheral venous cannulation of adults, a systematic review and network meta-analysis

Abstract: BackgroundPeripheral venous cannulation is an everyday practice in hospitals, which many adults find painful. However, anaesthesia for cannulation is usually only offered to children. Inadequate pain relief is not only unpleasant for patients but may cause anxiety about further treatment and deter patients from seeking medical care in the future. The aim of this study is to discover the most effective local anaesthetic for adult peripheral venous cannulation and to find out how the pain of local anaesthetic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 50 publications
2
47
0
Order By: Relevance
“…►Cite this as: Rüsch I nserting a cannula into a vein is a routine procedure, which in some patients may none the less cause discomfort (1,2). Surveys, editorials, and systematic reviews on this topic imply that local anesthesia is applied to the venipuncture sites on a regular basis in children, but this is handled rather inconsistently in adults (3)(4)(5)(6)(7). In a survey among anesthetists in the UK, the doctors reported that they administered a local anesthetic for venipuncture in cases where the cannula size exceeded 18 G. However, fewer than half of surgeons or specialists in internal medicine followed this practice (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…►Cite this as: Rüsch I nserting a cannula into a vein is a routine procedure, which in some patients may none the less cause discomfort (1,2). Surveys, editorials, and systematic reviews on this topic imply that local anesthesia is applied to the venipuncture sites on a regular basis in children, but this is handled rather inconsistently in adults (3)(4)(5)(6)(7). In a survey among anesthetists in the UK, the doctors reported that they administered a local anesthetic for venipuncture in cases where the cannula size exceeded 18 G. However, fewer than half of surgeons or specialists in internal medicine followed this practice (6).…”
mentioning
confidence: 99%
“…By contrast, numerous studies have consistently found that intradermal or subcutaneous application of a local anesthetic-for example, lidocaine solution 1-2%-reduces puncture-related pain (1, 8-10, 14, 15). A recent network meta-analysis directly or indirectly compared lidocaine application with 16 further analgetic interventions before peripheral venipuncture and found that 2% lidocaine was most effective (5). However, this procedure is time-consuming (7); it can result in a higher rate of puncture failures (15,16), and of itself causes pain (8)(9)(10)16).…”
mentioning
confidence: 99%
“…The region of cannulation also influences the pain intensity induced; for example, the antecubital fossa is associated with less pain than is the back of the hand . Nevertheless, many operators do not routinely offer pain relief because of time loss, considered lack of indication, belief that it makes the procedure more difficult, or peer pressure not to …”
Section: Introductionmentioning
confidence: 99%
“…11 Nevertheless, many operators do not routinely offer pain relief because of time loss, considered lack of indication, belief that it makes the procedure more difficult, or peer pressure not to. 10,12 It was recently shown that peripheral venous cannulation-induced pain (VCP) intensity can be used to predict the risk for postoperative pain in patients subjected to elective laparoscopic cholecystectomy. Patients scoring VCP at or above 2.0 VAS units had 3.4 times higher risk for moderate or severe postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, the waiting period to establish full analgesic effect is a significant barrier to their use, which has stimulated the development of new topical anesthetics and the revival of old ones, such as ethyl chloride. This anesthetic stopped being used after the development of new, safer drugs because of its possible adverse effects, but the controversy remains as to the use of ethyl chloride in clinical practice (Bond et al, 2016;Fossum, Love, & April, 2016;Hogan, Smart, Shah, & Taddio, 2014;Zempsky, 2008). This study aimed to compare the effectiveness of five topical anesthetics for preventing VP pain in children in an outpatient department of a pediatric hospital.…”
Section: Introductionmentioning
confidence: 99%